Clinical use of a new frameless optical neuronavigation system for brain biopsies: 10 cases (2013–2020). (9th February 2022) - Gutmann, S.; Tästensen, C.; Böttcher, I. C.; Dietzel, J.; Loderstedt, S.; Kohl, S.; Matiasek, K.; Flegel, T.
Abstract : Objectives: The aim of the retrospective study was to describe the brain biopsy procedure using a new frameless optical neuronavigation system and to report diagnostic yield and complications associated with the procedure. Materials and Methods: The medical records for all dogs with forebrain lesions that underwent brain biopsy with a frameless optical neuronavigation system in a single referral hospital between 2013 and 2020 were retrospectively analysed. Following data were collected: signalment, neurological signs, diagnostic findings, number of brain biopsy samples, sampled region, complications, duration of hospitalisation, whether the samples were diagnostic and histopathological diagnoses. The device consists of a computer workstation with navigation software, an infrared camera, patient tracker and reflective instruments. The biopsy needle was equipped with reflective spheres, so the surgeon could see the position of the needle during sampling the intracranial lesion free handed through a mini‐burr hole. Results: Ten dogs were included. Absolute diagnostic yield based on specific histopathological diagnosis was 73.9%. Three dogs had immune‐mediated necrotizing encephalitis, two dogs showed a necrotizing leukoencephalitis and two dogs a meningoencephalitis of unknown origin. In two dogs, the brain specimen showed unspecific changes. In one dog, the samples were non‐diagnostic. Seven dogs showed no neurological deterioration, one dog mild temporary ataxia and two dogs died within 36 hours post brain biopsy. Clinical Significance: In these 10 dogs, the frameless optical neuronavigation system employed was useful to gain diagnostic brain biopsy samples. Considering the mortality rate observed, further studies are needed to confirm the safety of this procedure and prove its actual clinical effectiveness.